Experimental infection of purebred Saanen goats high pathogenicity and virulence of Babesia aktasi - Ulucesme, Mehmet Can; Ozubek, Sezayi; Aktas, Munir (Public Library Science, 2024)
Small ruminant babesiosis remains a neglected disease despite causing significant economic losses to sheep and goat herds in many regions around the world. The pathogenesis and clinical manifestations of ovine babesiosis are well-known, but there is a lack of information regarding caprine babesiosis. Since the discovery of the first Babesia spp. in 1888, several species/subspecies/genotypes, including Babesia aktasi, have been described. Our recent molecular survey revealed that the parasite is highly prevalent (22.5%) in indigenous goats from Mediterranean region of T & uuml;rkiye. The aim of this experimental study was to determine the pathogenicity and virulence of B. aktasi in immunosuppressed (n = 5) and immunocompetent (n = 7) purebred Saanen goats. The goats were experimentally infected with fresh B. aktasi infected blood, and examined for clinical, parasitological, hematological, and serum biochemical findings throughout the infection. Following the parasite inoculation, intra-erythrocytic parasites were detected from the 1st day post-infection, followed by an increase in rectal temperature and parasitemia. The parasitemia was detected ranging from 4.3% to 33.5% in the immunosuppressed group, while it was 2.1% to 7.6% in the immunocompetent. Severe clinical symptoms characterized by anemia, jaundice, and hemoglobinuria developed in both groups. A statistically significant inverse correlation was observed between the increase in parasitemia and RBC, WBC, HCT, and Hb values in the goats compared to pre-infection levels. Values of AST, ALT, GGT, Total bilirubin, and Albumin showed a significant increase, with all the immunosuppressed goats dying on the 4th and 7th days post-infection, while four out of seven immunocompetent goats died on between 6-8th days. Severe edema in the lungs, frothy fluid in the trachea, jaundice in the subcutaneous and mesenteric fat, and dark red urine were detected in necropsy. The results obtained in this study demonstrated that B. aktasi was highly pathogenic to purebred Saanen goats. Current work assures valuable insights into the pathogenesis and virulence of B. aktasi and serves as a foundation for future studies to develop effective control strategies against caprine babesiosis.
Keywords: In-Vitro Activity; Brucella-Melitensis; Antimicrobial Susceptibility; Antibacterial Activity; Invitro Activity; Syrian Brucella; Strains; Resistance; Antibiotics; Identification